Some Worries About Deontic Closure - Kevin Kimble (Philosophies)
The Deontic Principle of Closure (DCL) appears initially to be a highly plausible principle. The DCL is commonly assumed in practical ethical reasoning, as when we make certain inferences about what we (morally) ought to do in particular situations. For example, if I am standing beside a burning house with several victims trapped inside and I have an obligation to rescue them, then if it is necessary for me to open the front door in order for me to lead them out, then it seems that I am morally bound in this situation to open the door. Similarly, if it is the case that I ought to keep my Friday morning 8:00 appointment with my student and it is a necessary condition for keeping the appointment that I wake up some time before 8:00, then I ought to wake up before 8:00. In spite of its attractiveness, however, various worries have been raised about the plausibility of this closure principle. In what follows, I shall critically examine DCL and discuss its plausibility in the face of various objections that have been raised against it. I shall argue that a slightly modified version of the principle circumvents the main objections and holds under several of the more or less standard interpretations of the “ought” operator.